Perilaku Impak Dan Porositas Paduan Al-Si-Mg Pada Pengecoran Sentrifugal Akibat Temperatur Pemanasan Awal Cetakan - Setyarini, Putu Hadi (Jurnal Rekayasa Mesin, 2011)
Aluminum is widely used as raw materials in engineering because this material is often used to replace other metals with the same function. This occurs when the product must have properties such as light, good heat conductivity, and low melting point. An example of making Aluminium product is centrifugal casting process. Centrifugal casting is a method of casting metal by pouring metal into a mold that rotates with a certain speed. This study aims to determine the effect of preheating temperature of the mold of on impact strength and porosity of aluminum alloy Al-Si-Mg in centrifugal casting. The experiments were carried out with and without mold pre-heating. The temperature of preheated mold were 100 º C, 200 º C, 300 º C, 400 º C. The data obtained were analyzed statistically and theoretically. The results showed that the increasing of the preheating temperature of the mold significantly affects the value of impact strength of aluminum alloy Al-Si-Mg. The highest value of impact strength and the lowest porosity were obtained in the preheating temperature of 400 º C. This is due to reduced temperature gradient between the temperature of molten metal and the mold temperature resulting in a slower cooling rate in a homogeneous suspension.Keywords : centrifugal casting, preheating the mold, aluminum alloy Al-Si-Mg, impact strength, porosity